2017
DOI: 10.14235/bs.2017.1087
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between the Presence of Agger Nasi Cells and the Development of Frontal Sinusitis: a Computer-Assisted Anatomic Study

Abstract: Objective: To use computed tomography (CT) to determine the relationship between agger nasi (AN) cells and the development of frontal sinusitis. Methods: In total, 996 patients (402 females and 594 males; average age, 37.2±12.8 years; range, 18-75 years) underwent a CT scan due to frontal sinusitis. The presence of AN cells was recorded. Patients were divided two groups according to the presence of the AN cell. The Lund-Mackay score (LMS) of each paranasal sinus shadow was evaluated in all patients. The LMS in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…[11] There are also differences in literature regarding the relationship between AN cell and frontal sinusitis. Eweiss et al, [10] Kubota et al, [12] and Del Gaudio et al [13] found no relation between AN cell and frontal sinusitis, wheras Yegin et al [14] reported the presence of sinusitis as significantly higher on the side of the AN cell. We also found a statistically significant relationship between frontal sinusitis and AN cell (p<0.001).…”
Section: Incidence Of Agger Nasi and Frontal Cells And Their Relationmentioning
confidence: 96%
“…[11] There are also differences in literature regarding the relationship between AN cell and frontal sinusitis. Eweiss et al, [10] Kubota et al, [12] and Del Gaudio et al [13] found no relation between AN cell and frontal sinusitis, wheras Yegin et al [14] reported the presence of sinusitis as significantly higher on the side of the AN cell. We also found a statistically significant relationship between frontal sinusitis and AN cell (p<0.001).…”
Section: Incidence Of Agger Nasi and Frontal Cells And Their Relationmentioning
confidence: 96%
“…ANC: Agger nasi cells are frontal ethmoidal cells, located in front of the anterior end of the middle concha and uncinate process in the nasal lateral wall. 9 …”
Section: Methodsmentioning
confidence: 99%